2014
DOI: 10.1080/02640414.2014.975736
|View full text |Cite
|
Sign up to set email alerts
|

Injury prevention in male veteran football players – a randomised controlled trial using “FIFA 11+”

Abstract: The warm-up programme "FIFA 11+" has been shown to reduce football injuries in different populations, but so far veteran players have not been investigated. Due to differences in age, skill level and gender, a simple transfer of these results to veteran football is not recommended. The purpose of this study was to investigate the preventive effects of the "FIFA 11+" in veteran football players. Twenty veteran football teams were recruited for a prospective 9-month (1 season) cluster-randomised trial. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
3
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 39 publications
3
90
3
16
Order By: Relevance
“…Some lesions, particularly to the muscles and tendons, can be prevented by ensuring good muscle condition, but others that arise during particular circumstances of the match are inevitable, and it is then that action must be taken to bring about a full recovery as soon as possible. Although some programs have been developed to prevent such injuries 3,4 , which have been the object of widespread consensus and have been publicized and analyzed, they still lack evidence 5,6 . Finding out what happens in championships offers the best way of predicting and preventing injuries 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Some lesions, particularly to the muscles and tendons, can be prevented by ensuring good muscle condition, but others that arise during particular circumstances of the match are inevitable, and it is then that action must be taken to bring about a full recovery as soon as possible. Although some programs have been developed to prevent such injuries 3,4 , which have been the object of widespread consensus and have been publicized and analyzed, they still lack evidence 5,6 . Finding out what happens in championships offers the best way of predicting and preventing injuries 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons retenu six études [1][2][3][4][5][6] pour un total de 930 sujets. Les publications présentaient des résultats très variables : le groupe d'intervention de deux études [1,5] présentait une réduction significative de la fréquence des blessures (p < 0,05 et p < 0,001).…”
Section: Résultatsunclassified
“…Une autre étude [4] n'a pas montré de résultats significatifs, même si le groupe d'intervention présentait des effets préventifs conséquents. Les trois autres études [2,3,6] ne montraient pas d'effets de pré-vention significatifs (p > 0,05).…”
Section: Résultatsunclassified
“…In a cluster RCT of the FIFA 11+ in veteran players (minimum age of 32), Hammes et al (2015) found no preventive effect of the FIFA 11+ on overall injuries. The authors attributed this lack of effect to the low frequency of performed sessions and suggested modifying the program (e.g., adding more ball-based and individual exercises) to better fit the specific implementation context.…”
mentioning
confidence: 96%
“…As support for the FIFA 11+'s efficacy grows (Al Attar et al, 2016), researchers have also explored the program's adaptability to other soccer populations, including veteran (Hammes et al, 2015), children (R€ ossler et al, 2016), and professional youth teams (O'Brien & Finch, 2016a). In a cluster RCT of the FIFA 11+ in veteran players (minimum age of 32), Hammes et al (2015) found no preventive effect of the FIFA 11+ on overall injuries.…”
mentioning
confidence: 99%